Transcriptional and Translational Regulation of α-Acetolactate Decarboxylase of Lactococcus lactis subsp. lactis - Goupil-Feuillerat, Nathalie (American Society for Microbiology, 2000)
The α-acetolactate decarboxylase (ALDC) gene, aldB, is the penultimate gene of the leu-ilv-ald operon, which encodes the three branched-chain amino acid (BCAA) biosynthesis genes in Lactococcus lactis. Its product plays a dual role in the cell: (i) it catalyzes the second step of the acetoin pathway, and (ii) it controls the pool of α-acetolactate during leucine and valine synthesis. It can be transcribed from the two promoters present upstream of the leu and ilv genes (P1 and P2) or independently under the control of its own promoter (P3). In this paper we show that the production of ALDC is limited by two mechanisms. First, the strength of P3 decreases greatly during starvation for BCAAs and under other conditions that generally provoke the stringent response. Second, although aldB is actively transcribed from P1 and P2 during BCAA starvation, ALDC is not significantly produced from these transcripts. The aldB ribosome binding site (RBS) appears to be entrapped in a stem-loop, which is itself part of a more complex RNA folding structure. The function of the structure was studied by mutagenesis, using translational fusions with luciferase genes to assess its activity. The presence of the single stem-loop entrapping the aldB RBS was responsible for a 100-fold decrease in the level of aldB translation. The presence of a supplementary secondary structure upstream of the stem-loop led to an additional fivefold decrease of aldB translation. Finally, the translation of the ilvA gene terminating in the latter structure decreased the level of translation of aldB fivefold more, leading to the complete extinction of the reporter gene activity. Since three leucines and one valine are present among the last six amino acids of the ilvA product, we propose that pausing of the ribosomes during translation could modulate the folding of the messenger, as a function of BCAA availability. The purpose of the structure-dependent regulation could be to ensure the minimal production of ALDC required for the control of the acetolactate pool during BCAA synthesis but to avoid its overproduction, which would dissipate acetolactate. Large amounts of ALDC, necessary for operation of the acetoin pathway, could be produced under favorable conditions from the P3 transcripts, which do not contain the secondary structures.